The relationship between normal motor development and disease impact-disability level in children with epilepsy - Tanrıverdi, Müberra; Karantay, Fatma Mutluay; Güler, Serhat; İşcan, Akın (Wiley-Blackwell, 2015)
[Abstract Not Available]
31st International Epilepsy Congress -- September 05-09, 2015 -- Istanbul, Turkey
WOS: 000365756500753
Keywords: Impact-Disability; Children; Epilepsy